Profitablitas dan Likuiditas terhadap Nilai Perusahaan melalui Kebijakan Dividen - Solihah; Ghonimah Zumroatun Ainiyah; Maharani, Destin Alfianika (Perwira Journal of Economics & Business, 2023)
This aim of this study was to determine the effect of profitability and liquidity on company value through dividend policy. The objects examined in this study is company listed on the Jakarta Islamic Index for the period 2014-2018.This type of research is quantitative research. The data used in this research is secondary data. The population in this study is company listed on the Jakarta Islamic Index during 2014-2018..The results showed that partially profitability and liquidity had a positive and significant effect on firm value. Profitability has a positive and significant effect on dividend policy. Liquidity has a positive and significant effect on dividend policy. Dividend policy has a positive and significant effect on firm value. Dividend policy cannot mediate the relationship between profitability and firm value. Dividend policies can mediate the relationship between liquidity and firm value.